Analysis of Groundwater Quality and Design of Low-Cost Water Purifier - K H, SHEMEERA; K.Prudhvi Raj; K.Prathyusha (International Journal of Engineering and Management Research, 2023)
The small portion of available fresh water for human consumption is being contaminated by various anthropogenic sources at a very alarming rate. Water pollution is the contamination of water bodies, usually as a result of human activities. Water pollution is one of many types of pollution which results from contaminants being introduced into the natural environment. Pollution causes adverse change. Pollution of groundwater can occur from on-site sanitation systems, landfills, effluents from wastewater treatment plants, petrol filling stations, leaching sewers, or over-application of fertilizers in agriculture. With this view, an attempt was made to assess the quality of groundwater in the rural area near Vijayawada by examining various physicochemical parameters such as colour, turbidity, odour, pH, total dissolved solids, alkalinity, hardness, chloride, fluoride, iron, and magnesium to check the suitability of water for human consumption. In this work, samples of water were collected and various parameters regarding the water quality were analysed &compared with Indian Standards: 10500 (Drinking water specifications) to check the acceptability of water for drinking purposes. Further, an attempt is also made to design a low-cost groundwater purifier that works on the process of adsorption using naturally available materials. Keywords: Water purifier, chloride, adsorption,